20 shi ji 30 nian dai Zhongguo "shang zi gui nong" wen ti yan jiu = 20shiji 30niandai zhongguo "shangzi guinong" wenti yanjiu - Xu, Yongfeng (Beijing : Zhongguo she hui ke xue chu ban she, 2012)
Summary in vernacular field only.
Includes bibliographical references (pages [296]-305).
Keywords: Agriculture -- China -- Finance -- History; Agriculture -- Economic aspects -- China -- History -- 20th century; Agriculture and state -- China -- History -- 20th century; Rural development -- China